Two-dimensional half-metallicity in transition metal atoms decorated Cr2Ge2Te6 - Kang, Wei; Du, Xue; Wang, Jintian; Ye, Ziqin; Zhao, Jinghong; Wang, Wei; Wang, Yan; Wang, Lin; Liu, Xiaoqing (Frontiers in Physics, 2023)
As one of the first experimentally found and naturally stable two-dimensional (2D) ferromagnetic materials, the monolayer Cr2Ge2Te6 has garnered great interest due to its potential hires in electronics and spintronics. Yet, the Curie temperature of monolayer Cr2Ge2Te6 is lower than the ambient temperature, severely restricting the creation of valuable devices. Using the first-principle calculations, we explored how the adsorption of 3d transition metals affects the electronic and magnetic properties of the monolayer Cr2Ge2Te6 (from Sc to Zn). Our findings indicate that depending on the 3d transition metals to be adsorbed, the electronic properties of the Cr2Ge2Te6 adsorption system may be adjusted from semiconductor to metal/half-metal. We found that the adsorption of Ti and Fe leads to a transformation from semiconductor to metal. While in Cr2Ge2Te6@Sc, V, Co, Ni, and Cu, the absorption realizes the changes from semiconductor to half metal. Moreover, adsorption may modify the magnetic moment and Curie temperature of the adsorbed system to enhance the ferromagnetic stability of the monolayer Cr2Ge2Te6. Furthermore, we are able to modulate the half-metallic of Cr2Ge2Te6@Mn by means of electric fields. Hence, adsorption is a viable method for modulating the ferromagnetic half-metallic of 2D ferromagnets, paving the door for the future development of nano-electronic and spintronic devices with enhanced performance for 2D ferromagnetic materials.